Introduction to JAVA programming : brief verison - Liang, Y. Daniel (Pearson, 2019)
This text is intended for a 1-semester CS1 course sequence. The Brief Version contains the first 18 chapters of the Comprehensive Version. The first 13 chapters are appropriate for preparing the AP Computer Science exam. For courses in Java Programming. A fundamentals-first introduction to basic programming concepts and techniqu.